Applying a Systemic Approach to Gender Transport Poverty: Pakistan in Context - Faiz, Komal; Woodcock, Andree; McDonagh, Deana; Iqbal, Sana (FormAkademisk, 2020)
Transport poverty and the associated levels of deprivation experienced by women is a ‘wicked problem'. A systemic approach is needed to address entrenched societal and cultural norms that deprive women of equality and agency. The conceptual shift from ‘transport’ to ‘mobility’, emphasising access to life opportunities, provides an opportunity for more systems approaches to be tried. The ‘WEMOBILE project’ addressed gender transport poverty in Low-Middle-Income Countries using ethnographic and empathic design approaches to understand and re(present) the effects of gender transport poverty. This article focusses on insights provided by employing a systemic design to data gathered in Pakistan. In representting data as system maps, gaps that hinder the effectiveness of existing solutions are emphasised as well as the usefulness of this approach in highlighting opportunities for policy and operational changes. Keywords: Empathy, gender-sensitive transport, systems-thinking, Low-Middle-Income Countries, Pakistan.